Cross-Agencies And Community Collaboration For Tourism In Lebak Regency, Banten Province, Indonesia - Sak Khie; Lindawati Lindawati (JURNAL DESTINASI PARIWISATA, 2022)
Tourism is the leading sector in Lebak Regency to encourage economic growth. However, the Covid-19pandemic affects tourist visits and the growth of businesses and SMEs. This study described tourism promotioninnovations in Lebak Regency, Banten Province, Indonesia, namely the Lebak Regency Calendar of Events(CoE). A case study was used, with literature reviews and interviews to collect data. The CoE was in line withthe annual development plan, which began with the Development Planning Conference (Musrenbang) and theframing of Local Government Work Plans (RKPD). The culture and tourism agency took the role of 'packaging'and synchronised each agency's programme in Lebak Regency as tourism events or facilitated as part of thetourism events. Each tourism event in Lebak Regency involved various agencies and sectors, the artscommunity, creative economy actors, and SMEs in Lebak Regency. This innovation encourages tourismpromotion massively in Lebak Regency to increase tourist visits and reactivate community economic activity.Keyword: Development Program, Economic Growth, Innovation, Tourism